(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
This study was conducted to determine the contamination of microorganisms, pH, water activity (aw), as well as sensory tests (color, aroma, flavor, and texture) with the presentation of different cheeses. This research was conducted in an Laboratorium Terpadu and Laboratorium Phatogen, Teknologi Hasil Ternak, Program Study Ilmu Produksi dan Teknologi Peternakan, Fakultas Peternakan, Bogor Agricultural University. Data from the observations in doing calculations using t-test mathematical model of this design is t = with 2 times each replicate. The variables measured were the value of Total Plate Count (TPC), Potato Dextrote Agar (PDA), pH, aw, and a sensory test. Data were analyzed using t-test model. The results of the analysis of the t-test (α = 5%) of cheddar cheese block and cheddar cheese slice stem not give significant differences (P > 0,05) on the TPC and PDA yeasts or fungi. t-test (α = 5%) to pH and aw on each individual cheese does not give significant differences (P> 0,05). From the results of sensory analysis on the color of the cheese is seen that the panelists really liked the cheese sticks. Rate on cheese stem higher with the average value of which is 4 compared with cheddar cheese shaped slice which has an average value is 3,7. as well as on the assessment of texture and flavor, the rod-shaped cheddar cheese has a value - average higher than shaped slice of cheddar cheese. while the aroma cheddar cheese slice has a higher average value than the rod-shaped cheddar cheese. However this is seen not provide a significant difference due to differences in cheese and cheese slice stem relatively small. On the results of the analysis (t-test) showed that the difference in assessment of color, texture, aroma and taste of the cheese slice and cheese stems not significant or not significant. This is most likely because of the cheese slice and rods produced by the company that produced simultaneously.